Why We Should Not Pay for Human Organs - Delmonico, Francis L. (Zygon, 2003)
The right to buy and sell human organs is challenged by the authors within the framework of a broad Christian perspective. Opposition to organ sales is argued in the light of the developing underclass of poor organ donors throughout the world who sell their organs to the rich. Very often neither the donors nor the recipients are fully informed about the medical risks involved in the procedure of organ transplantation.